The Effectiveness of Digital Recruitment Strategies on Workforce Quality in the Industrial Era 4.0 - Azim, Muhammad; Alfarisi, Moh. Salman; Uli, Aprilla Sinta; Rosdiyanti, Evi; Padila, Yani (Business Management, 2025)
Abstract . The digital transformation that occurred in the Industry 4.0 era has encouraged organizations to adopt new approaches in human resource management, especially in the recruitment process. This research aims to analyze the effectiveness of digital recruitment strategies on the quality of the workforce recruited. The research method used is a quantitative approach with an explanatory design. Data was collected by distributing questionnaires to 120 respondents who were recruitment practitioners in service and technology sector companies, and analyzed using multiple linear regression. The research results show that digital recruitment strategies have a positive and significant effect on workforce quality, with a regression coefficient value of β = 0.567 and a significance level of p < 0.001. These findings indicate that the use of technology in the recruitment process, such as professional social media, algorithm-based selection systems, and online interviews, contributes to increasing selection accuracy and suitability of candidate competencies. This research provides a theoretical contribution to the development of technology-based recruitment studies, while also presenting practical implications for organizations in developing adaptive and competitive recruitment strategies in the digital era.